2005
DOI: 10.1167/iovs.04-0653
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Cone-Specific Gene Expression and Degeneration of Cone Photoreceptors in theRpe65−/−Mouse at Early Ages

Abstract: In the Rpe65(-/-) mouse, the expression of cone-specific genes is downregulated and is accompanied by cone degeneration at early ages. Early administration of 9- or 11-cis retinal can partially prevent cone loss, suggesting that the absence of 11-cis chromophore may be responsible for the early cone degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
131
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(147 citation statements)
references
References 24 publications
14
131
1
1
Order By: Relevance
“…This inhibition may result in a deficient supply of 11-cis retinal chromophore, particularly for the macula which has higher demand for chromophore recycling. Lack of chromophore could destabilize opsin protein and subsequently lead to photoreceptor degeneration (41). The data presented here clearly demonstrate that micromolar concentrations of A2E inhibited isomerization/ hydrolysis of all-trans retinyl esters to 11-cis retinol catalyzed by RPE65, but did not affect the retinyl ester synthesis by LRAT.…”
Section: Discussionmentioning
confidence: 63%
“…This inhibition may result in a deficient supply of 11-cis retinal chromophore, particularly for the macula which has higher demand for chromophore recycling. Lack of chromophore could destabilize opsin protein and subsequently lead to photoreceptor degeneration (41). The data presented here clearly demonstrate that micromolar concentrations of A2E inhibited isomerization/ hydrolysis of all-trans retinyl esters to 11-cis retinol catalyzed by RPE65, but did not affect the retinyl ester synthesis by LRAT.…”
Section: Discussionmentioning
confidence: 63%
“…Rpe65 −/− , a severe cone degeneration model, displays rapid ventral and central cone loss, whereas dorsal cones are preserved relatively well (20,21). Our cone density evaluation by peanut agglutinin (PNA) and cone arrestin (CAR) labeling in Rpe65 −/− mice showed a degeneration pattern similar to that reported previously (20,25), i.e., the ventral and central retina shows early onset, fast cone degeneration (about 10% of the wild-type level remained at postnatal day 30, P30), whereas the peripheral dorsal retina degenerated more slowly (about 50% of the wild-type level remained at P30) ( Fig. 1 A and B).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether TH signaling affects cone viability in inherited retinal degeneration, we investigated cone death/survival in retinal degeneration mouse models following TH signaling suppression and stimulation. Retinol isomerase RPE65-deficient (Rpe65 −/− ) (a model of Leber congenital amaurosis, LCA) (20,21) and cone photoreceptor function loss type 1 (cpfl1) mice (PDE6C mutation, a model of achromatopsia) (22), displaying fast and severe cone degeneration, were used to determine whether suppressing TH signaling with antithyroid treatment reduces cone degeneration. Cone cyclic nucleotide-gated channel B subunit-deficient (Cngb3 −/− ) (a model of achromatopsia) (23) and guanylate cyclase 2e-deficient (Gucy2e −/− ) (another model of LCA) mice (24), displaying relatively slow progressive and moderate cone degeneration, were used to determine whether stimulating TH signaling (with T3…”
mentioning
confidence: 99%
“…For example, there is no prescribed role for RPE65 in the retinoid cycle for cones in the cone dominated retina. However, knockout of this gene in the rod dominated retina of the mouse causes complete loss of cone function (Znoiko, Rohrer, Lu, Lohr, Crouch and Ma, 2005). Furthermore, it has also been shown that knocking out RPE65 in the 'all cone' Nrl −/− retina and in the 'cone only' retina of the Rho −/− mouse, causes cones to be functionless (Seeliger, Grimm, Stahlberg, Friedburg, Jaissle, Zrenner, Guo, Reme, Humphries, Hofmann, Biel, Fariss, Redmond and Wenzel, 2001;Wenzel, von, Oberhauser, Tanimoto, Grimm and Seeliger, 2007).…”
Section: Introductionmentioning
confidence: 99%